QUO VADIS, OCCASIO? (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
With its origin in Antiquity, the Occasion concept is identified as “ the time of human life, so different from that of the great cycles of nature and history and plastic personified by the deity of Kairos in Greek mythology (Ursache Tcaciuc, Anca)” and the divinity of Occasio to Roman civilization, the notion is taken by the Jesuit Jan David and converted to the spiritual and religious needs of his time. All the ancient sources presented the deity as the best moment, the opportunity, the occasion in time to realize something good. From the totally independence and jovial manifestation, the Occasion becomes one with the meditator, an opportunity to fallow Christ and to proceed in Divine Salvation.